1994
DOI: 10.1161/01.hyp.24.6.808
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antihypertensive agents on baroreceptor function in early hypertensive rats.

Abstract: To investigate the effects of antihypertensive treatment with four currently used agents (trichlormethiazide, atenolol, nicardipine, and enalapril) on the arterial baroreceptor function at the early phase of hypertension, we administered the agents to spontaneously hypertensive rats and WistarKyoto rats from 8 to 10 weeks of age and examined the aortic nerve activity function. In untreated spontaneously hypertensive rats, the relation between the arterial pressure and aortic nerve activity was shifted to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[1][2][3] We have reported impairment of the baroreflex function in hypertension based on recordings of renal SNA (RSNA) in conscious rabbits and rats and on vagal afferent nerve activity. 4,5 We have also confirmed that the angiotensin (Ang) II type 1 (AT 1 ) receptor antagonist candesartan improves the impaired baroreflex in conscious rats with congestive heart failure. 6 Earlier studies examined the responses of BP and SNA to Ang II and Ang II antagonists microinjected into the RVLM of normotensive and hypertensive animals, [7][8][9][10][11] because the RVLM area contains Ang II-immunoreactive nerve terminals and a moderately high density of AT 1 receptors.…”
mentioning
confidence: 64%
“…[1][2][3] We have reported impairment of the baroreflex function in hypertension based on recordings of renal SNA (RSNA) in conscious rabbits and rats and on vagal afferent nerve activity. 4,5 We have also confirmed that the angiotensin (Ang) II type 1 (AT 1 ) receptor antagonist candesartan improves the impaired baroreflex in conscious rats with congestive heart failure. 6 Earlier studies examined the responses of BP and SNA to Ang II and Ang II antagonists microinjected into the RVLM of normotensive and hypertensive animals, [7][8][9][10][11] because the RVLM area contains Ang II-immunoreactive nerve terminals and a moderately high density of AT 1 receptors.…”
mentioning
confidence: 64%
“…Two studies 30,31 in which antihypertensive agents were used to treat hypertension indicate that reduction in SAP by itself may directly potentiate the function of BRR. As such, it is possible that restoration of BRR sensitivity by ASON1 in SHR and SHRSP may result from the depressor effect of this antisense oligonucleotide.…”
Section: Discussionmentioning
confidence: 99%
“…The electrical activity was amplified using an amplifier (AB-651J, Nihon Kohden) with a band pass filter of 50-3000 Hz. The amplified activity was rectified and integrated using an integrator (EI-601GS, Nihon Kohden) with a 2 s time constant (Ichikawa et al 1994, Waki et al 1997. MBP was raised by 30-50 mmHg by a bolus injection of phenylephrine (20-50 lg kg )1 ).…”
Section: Assessment Of Functional Characteristics Of Input Pathway Inmentioning
confidence: 99%